Analysis of Thermite Rail Joint Damage in Curve Section 3 of Lrt Jakarta - Heriyanto Wibowo; Insan Kamal; Dhea Ananda Safitri (Green Publisher, 2025)
This study analyzes the damage to the Alumino Thermit Welding (ATW) rail joints in the curved Section 3 between Pulomas Station and Boulevard Selatan Station of the Jakarta LRT. Using a qualitative method with a cause-and-effect approach through a fishbone diagram, the study identifies the factors causing the damage. The results show that the damage is classified as Surface Defect. The primary contributing factors are the small curve radius, imbalance of train wheels, and the driving technique of the train operator, with the highest frequency at 46.15%. This is followed by inspections conducted only visually at night with limited lighting, contributing 38.46%. Material factors have the smallest contribution, at 15.38%. For repairs, it is recommended to use methods such as patching with electric welding, grinding, and re-welding, along with routine inspections using Ultrasonic Testing. Coordination with the OCC and Crew Unit Leaders (train operators) regarding the recommended speed limits on curves is crucial, and the implementation of sensor technology for real-time monitoring of rail conditions should also be considered.